Nutritional considerations and strategies to facilitate injury recovery and rehabilitation - Smith-Ryan, A. E.; Hirsch, K. R.; Saylor, H. E.; Gould, L. M.; Blue, M. N. M. (Journal of Athletic Training, 2020)
Nutritional interventions are not commonly a standard of care in rehabilitation interventions. A nutritional approach has the potential to be a low-cost, high-volume strategy that complements the existing standard of care. In this commentary, our aim is to provide an evidence-based, practical guide for athletes with injuries treated surgically or conservatively, along with healing and rehabilitation considerations. Injuries are a normal and expected part of exercise participation. Regardless of severity, an injury typically results in the athlete's short- or long-term removal from participation. Nutritional interventions may augment the recovery process and support optimal healing; therefore, incorporating nutritional strategies is important at each stage of the healing process. Preoperative nutrition and nutritional demands during rehabilitation are key factors to consider. The physiological response to wounds, immobilization, and traumatic brain injuries may be improved by optimizing macronutrient composition, caloric consumption, and nutrient timing and using select dietary supplements. Previous research supports practical nutrition recommendations to reduce surgical complications, minimize deficits after immobilization, and maximize the chance of safe return to play. These recommendations include identifying the individual's caloric requirements to ensure that energy needs are being met. A higher protein intake, with special attention to evenly distributed consumption throughout the day, will help to minimize loss of muscle and strength during immobilization. Dietary-supplement strategies may be useful when navigating the challenges of appropriate caloric intake and timing and a reduced appetite. The rehabilitation process also requires a strong nutritional plan to enhance recovery from injury. Athletic trainers, physical therapists, and other health care professionals should provide basic nutritional recommendations during rehabilitation, discuss the timing of meals with respect to therapy, and refer the patient to a registered dietitian if warranted. Because nutrition plays an essential role in injury recovery and rehabilitation, nutritional interventions should become a component of standard-of-care practice after injury. In this article, we address best practices for implementing nutritional strategies among patients with athletic injuries.